Hybrid nanoliposome as a targeted growth inhibitor for Cervical Carcinoma Cell line - Awad, Noor A.; Yassen, Nahi Y.; Tawfeeq, Amer T.; Turki, Kismat M. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: targeted cancer nanotherapy represents a golden goal for nanobiotechnology to overcome the severe side effects of conventional chemotherapy. Hybrid nanoliposomes (HLs) composed of L-α-dimyristoylphosphatidylcholine (DMPC) and Polyoxyethylene (23) dodecyl ether (C12 (EO)23 ) can integrate selectively into the cancer cell membrane inducing cancer cell death. Objectives: to assess the capacity of locally (in hose) synthesized hybrid nanoliposome to inhibit the growth of cervix cancer cells (HeLa) and induce apoptosis. Patients and Methods: hybrid nanoliposomes(nHLs) synthesized by sonication method from a mixture of 90% mol DMPC and 10% mol C12(EO)23 in tissue culture media RPMI-1640 for 6 hours at 300W and 40ºC then filtration with 0.2μm filter. Shape and size characterized with scanning electron microscope (SEM). Viability of HeLa cell and normal lymphocytes challenged with HLs were determined using MTT assay. Induction of apoptosis in the challenged cells was examined by staining with fluorescence dye mix acridine orange/propidium iodide. Results: synthesized nHLs were in nanozise range and selectively inhibited HeLa cells proliferation with IC50 of 0.2mM DMPC with no effect against normal lymphocytes. Apoptosis was evident in 88.24% of HeLa cells population treated with HLs. Conclusion: synthesized nHLs may considered as promising nanotherapy, this study recommends further inspections for the mechanism of action of nHLs and their capabilities to inhibit other types of cancers both in vitro and in vivo